BESAMBAT: Playing while getting to know the family’s medical plants - Nina Karlina; Amanda Safitri; Endah Yuningsih; Arfa Maulana Kusumawijaya; Putri Ayu Fiddiyana; Elis Setiawati; Ellen Maylina; Mudrikah Zaen; Solehah Nurfadilah; Yahya Adi Rahman; Zahrah Zakiyyah Mukaromah; Winny Setyonugroho; Muchammad Agung Miftahuddin; Lela Sulastri; Aris Slamet Widodo; Didin Ahidin (Universitas Muhammadiyah Magelang, 2023)
The use of family medicinal plants (TOGA) continues to play an important role as first aid for families before seeking treatment from medical personnel. Introducing the types of medicinal plants and their benefits is crucial as a learning medium for elementary school-age students. The aim of this activity is to increase knowledge by introducing types of medicinal plants and their benefits to students at Klangenan 2 Elementary School, Cirebon Regency. This activity is conducted through counseling and game methods. The result of this service activity is an increase in students' understanding of family medicinal plants and their benefits.